Diversity of helminth parasites of freshwater fish in the headwaters of the Coatzacoalcos River, in Oaxaca, Mexico - Salgado-Maldonado, Guillermo (Int J Parasitol Parasites Wildl, 2020)
We documented the diversity of helminth parasites of 25 fish species from 8 families occurring in the headwaters of the Coatzacoalcos river basin. This river flows along the border between the states of Oaxaca and Veracruz, in the region of the Isthmus of Tehuantepec, in south-eastern Mexico, and in northern Central America. We recorded 48 species, representing 44 genera and 29 helminth families. Six of the 25 fish species were examined for helminths for the first time; 60 new host records were reported. Nematodes and trematodes were the most abundant taxonomic groups. The helminth fauna from our study area consists of primarily central American species. Most species recorded from this area have also been captured from freshwater bodies between the Isthmus of Tehuantepec and the Isthmus of Panama. However, three species, including an acanthocephalan and two nematodes, are likely endemic to this area. We argue that, in contrast to the presence of larval helminths, which mostly depends on the geographical location of water bodies, adult helminths are an integral and consistent component of the regional community. Data on taxonomic composition and distribution of helminth fauna reported in this paper, contribute to a better understanding of this faunal component in northern Central America (CA). Furthermore, knowledge of helminth parasites of freshwater fish from Neotropical Mexico and CA facilitates prediction of which parasite species is likely to infect fish in a specific geographical area.